The changes in physicochemical properties and microbiota composition of grass carp (Ctenopharyngodon idellus) under different aquaculture modes during 4°C storage. Issue 1 (7th December 2021) - Tian, Li; Luo, Tao; Zhuang, Shuai; Li, Yan; Hong, Hui; Shu, Rui; Tan, Yuqing; Luo, Yongkang
Abstract: Different aquaculture modes have been developed in the past decade. This study evaluated the impact of different fish aquaculture modes on the physiochemical changes and microbiota composition of grass carp fillets during 4°C storage. The total viable counts of container‐cultured grass carp were 1 day later than that of pond‐cultured group to exceed 7 log CFU/g. Its sensory scores were higher than that of pond‐cultured group after day 9. The total volatile basic nitrogen and hypoxanthine in container‐cultured group were 26.00% and 47.78% lower than that in pond‐cultured group on day 11, respectively. However, the concentration of trichloroacetic acid –soluble peptides and putrescine in container‐cultured group were higher than the pond‐cultured group on day 11. The initial microbiota of grass carp fillets in both groups was Acinetobacter . However, the dominant spoilage bacteria in pond‐cultured and container‐cultured grass carp on day 11 were Shewanella and Pseudomonas, respectively. Novelty impact statement: On the one hand, our study firstly reported the dominant spoilage bacteria in pond‐cultured and container‐cultured grass carp were different, which may cause the different quality of grass carp under the two different aquaculture modes. On the other hand, our results showed that the shelf life of container‐cultured grass carp was at least 14.29% longer than the pond‐cultured group. In conclusion, our results can provide information for researchers and industries to compare the advantages and disadvantages of different aquaculture modes and develop the quality control technology of fish cultured in different modes in the future.